Gender Differences in Preference of the Wage Level and Risk on the Czech Labour Market - Dagmar Brozova; Dominik Stroukal (European Scientific Journal, ESJ, 2018)
This work focuses on the preference theory and shows that this theory is valid also in the Czech labour market. In this paper, we posed three hypotheses, which we verified using four models with 2011 data about 1984 Czech employees. The first hypothesis says that women will prefer intrinsic rewards compared to high wages more likely than men. This hypothesis was verified. It turns out that women prefer higher wages against other nonmonetary job characteristics with 6% lower probability. The second hypothesis that women with a university education will prefer intrinsic rewards with the same probability as men the same degree was also verified. Czech data, however, shows that university education is associated with 40% higher preferences of intrinsic rewards, which is inconsistent with previous findings. Thirdly, it was shown that women prefer less risk than men, by 0.7 points on a scale of 0-10, while gender does not matter among people with university education.